Book of lives : a memoir of sorts [large type] - Atwood, Margaret, 1939- (Random House Large Print, 2025)
"Every writer is at least two beings: the one who lives, and the one who writes. Though everything written must have passed through their minds, or mind, they are not the same." Raised by ruggedly independent, scientifically minded parents--entomologist father, dietitian mother--Atwood spent most of each year in the wild forest of northern Quebec. This childhood was unfettered and nomadic, sometimes isolated (on her eighth birthday: "It sounds forlorn. It was forlorn. It gets more forlorn."), but also thrilling and beautiful. From this unconventional start, Atwood unfolds the story of her life, linking seminal moments to the books that have shaped our literary landscape, from the cruel year that spawned Cat's Eye to the Orwellian 1980s Berlin where she wrote The Handmaid's Tale. In pages bursting with bohemian gatherings, her magical life with the wildly charismatic writer Graeme Gibson and major political turning points, we meet poets, bears, Hollywood actors and larger-than-life characters straight from the pages of an Atwood novel. As we travel with her along the course of her life, more and more is revealed about her writing, the connections between real life and art--and the workings of one of our greatest imaginations.